ANALISIS PENDAPATAN USAHATANI BERAS MERAH (Oryza glaberrima) DI DESA NUNKURUS KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Fetriani Angela Haba; Marthen Robinson Pellokila; Maria Bano (Buletin Ilmiah Impas, 2021)
This research was carried out in the village of Nunkurus East Kupang subdistrict Kupang Regency East Nusa Tenggara province from April to June 2019, with the aim at knowing: (1).The amount incomes of farmers from the village of Nunkurus in the district of East Kupang, Kupang. (2).The feasibility of red rice farming in the village of Nunkurus East Kupang District in Kupang Regency. Sensus method was used to collect the data. The data comprised primary and secondary data. Primary data was collected by interviewing 30 farmer respondents. Secondary data was obtained from relevant agencies or agencies as well as from library studies. The results showed that : (1).Net income of red rice farming of the respondent was Rp.1,097,423,458 in one planting season with an average of Rp. 36, 580,782 per respondents growing season. (2).The R/C ratio 4.2, which means that each Rp. 1,-, spent by the farmer on the cost of rice farming will revenue of Rp. 4.2,-. Since the R/C ratio is greater than 1 (R/C > 1), red rice farming is economically and viable.